Answer:
<h3>
( - 1 , - 1 )</h3>
Option D is the correct option.
Step-by-step explanation:
y = - 2x - 3 → Equation ( i )
y = 3x + 2 → Equation ( ii )
Using elimination method
y + 2x = - 3
y - 3x = 2
---------------------
5x = - 5
Divide both sides of the equation by 5
![\frac{5x}{5} = \frac{ - 5}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5x%7D%7B5%7D%20%20%3D%20%20%5Cfrac%7B%20-%205%7D%7B5%7D%20)
Calculate
![x = - 1](https://tex.z-dn.net/?f=x%20%3D%20%20-%201)
Again, Putting the value of x in equation ( ii ) in order t get the value of y
![y = 3x + 2](https://tex.z-dn.net/?f=y%20%3D%203x%20%2B%202)
plug the value of x
![= 3 \times ( - 1) + 2](https://tex.z-dn.net/?f=%20%3D%203%20%20%5Ctimes%20%28%20-%201%29%20%2B%202)
Any expression multiplied by ( - 1 ) equals it's opposite
![= - 3 + 2](https://tex.z-dn.net/?f=%20%3D%20%20-%203%20%2B%202)
Calculate
![= - 1](https://tex.z-dn.net/?f=%20%3D%20%20-%201)
Therefore, The possible solution of the system is the ordered pair ( x , y )
![(x \:, y \: ) = ( - 1 \:, - 1)](https://tex.z-dn.net/?f=%28x%20%5C%3A%2C%20y%20%5C%3A%20%29%20%3D%20%20%28%20-%201%20%5C%3A%2C%20-%201%29)
-----------------------------------------------------------------------
Check if the given ordered pair is the solution of the system of equation
![- 1 = - 2 \times ( - 1) - 3](https://tex.z-dn.net/?f=%20-%201%20%3D%20%20-%202%20%5Ctimes%20%28%20-%201%29%20%20-%203)
![- 1 = 3 \times ( - 1) + 2](https://tex.z-dn.net/?f=%20-%201%20%3D%203%20%5Ctimes%20%28%20-%201%29%20%2B%202)
Simplify the equation
![- 1 = - 1](https://tex.z-dn.net/?f=%20-%201%20%3D%20%20-%201)
![- 1 = - 1](https://tex.z-dn.net/?f=%20-%201%20%3D%20%20-%201)
Since all the equalities are true, the ordered pair is the solution of the system.
<h3>
( x , y ) = ( - 1 , - 1 )</h3>
Hope this helps..
Best regards!!